2014
DOI: 10.1371/journal.pone.0103750
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Diatom Nanostructured Biosilica in Arachnoidiscus sp: Micro-Optics from Mother Nature

Abstract: Some natural structures show three-dimensional morphologies on the micro- and nano- scale, characterized by levels of symmetry and complexity well far beyond those fabricated by best technologies available. This is the case of diatoms, unicellular microalgae, whose protoplasm is enclosed in a nanoporous microshell, made of hydrogenated amorphous silica, called frustule. We have studied the optical properties of Arachnoidiscus sp. single valves both in visible and ultraviolet range. We found photonic effects du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 21 publications
2
75
0
Order By: Relevance
“…nano-to micrometer scaled sieves [5] or drug carriers [6] , [7] as well as vectors for drug delivery [8] , protein adsorbents [9] and as photocatalysts [10] . Diatom frustules also show particular optical properties [11] , [12] , [13] , [14] , [15] , [16] , [17] making them interesting for several optical applications [18] . Furthermore, the biosilica can also be used as a powder to reinforce other composites [19] .…”
Section: Introductionmentioning
confidence: 99%
“…nano-to micrometer scaled sieves [5] or drug carriers [6] , [7] as well as vectors for drug delivery [8] , protein adsorbents [9] and as photocatalysts [10] . Diatom frustules also show particular optical properties [11] , [12] , [13] , [14] , [15] , [16] , [17] making them interesting for several optical applications [18] . Furthermore, the biosilica can also be used as a powder to reinforce other composites [19] .…”
Section: Introductionmentioning
confidence: 99%
“…We are interested in developing a simple description of the multiple interference points described in simulations at a distance corresponding to outside the frustule when light interacts with the valve of the centric species Coscinodiscus granii (C. granii) [10,[12][13][14][15]. These interference points have been discussed on a theoretical basis and a few have been showed experimentally [13][14][15][16][17]. To our knowledge, it is the first time that multiple interference points have been shown both experimentally and their positions connected to theoretical prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Such filtering behavior was also shown for circular valve from Arachnoidiscus sp. for which green and red wavelengths were shown to be more concentrated than blue light (Ferrara et al, 2014). In addition, in the case of UVB light it was shown that the light spot was very weak, and far away from the valve.…”
Section: Light Filtrationmentioning
confidence: 97%
“…Furthermore, similar focusing behavior was shown for the centric single valve of Arachnoidiscus sp. where a 633 nm laser beam was confined at 163 µm from the valve (Ferrara et al, 2014).…”
Section: Light Focusing and Concentrationmentioning
confidence: 99%